2023
DOI: 10.1007/s11119-023-10064-2
|View full text |Cite
|
Sign up to set email alerts
|

High-precision estimation of grass quality and quantity using UAS-based VNIR and SWIR hyperspectral cameras and machine learning

Raquel Alves Oliveira,
Roope Näsi,
Panu Korhonen
et al.

Abstract: Miniaturised hyperspectral cameras are becoming more easily accessible and smaller, enabling efficient monitoring of agricultural crops using unoccupied aerial systems (UAS). This study’s objectives were to develop and assess the performance of UAS-based hyperspectral cameras in the estimation of quantity and quality parameters of grass sward, including the fresh and dry matter yield, the nitrogen concentration (Ncont) in dry matter (DM), the digestibility of organic matter in DM (the D-value), neutral deterge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…Furthermore, this study has not investigated grassland quality. Oliveira et al 49 recently demonstrated the potential of hyperspectral UAV imaging sensors in providing these quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study has not investigated grassland quality. Oliveira et al 49 recently demonstrated the potential of hyperspectral UAV imaging sensors in providing these quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The HS camera sampled spectral signatures with a relatively high spectral resolution (average of 8.98 nm) and FWHM (average of 6.9 nm) in the visible to near-infrared spectral range (500-900 nm). It is worth recognizing that the state-of-the-art technology offers enhanced-performance figures, for example, a spectral resolution of 2.6 nm and an FWHM of 5.5 nm in the spectral range of 400-1000 nm, as well as extending the spectral range beyond visible and near-infrared to the short-wave-infrared region [59]. Furthermore, this study does not apply spectral-band selection or handcrafted spectral features or indices that are commonly used in the context of classical machine learning approaches [13,20,59].…”
Section: Further Researchmentioning
confidence: 99%
“…It is worth recognizing that the state-of-the-art technology offers enhanced-performance figures, for example, a spectral resolution of 2.6 nm and an FWHM of 5.5 nm in the spectral range of 400-1000 nm, as well as extending the spectral range beyond visible and near-infrared to the short-wave-infrared region [59]. Furthermore, this study does not apply spectral-band selection or handcrafted spectral features or indices that are commonly used in the context of classical machine learning approaches [13,20,59]. Instead, we considered that the DNN models could find the relevant features from the spectral signatures.…”
Section: Further Researchmentioning
confidence: 99%